VITAMIN DEFICIENCY CASES RESULTING FROM PARASITIC DISEASES - Aslonova Marjona Ramazonovna (Galaxy International Interdisciplinary Research Journal, 2023)
Reducing parasitic diseases is one of the pressing issues. To overcome this problem requires the study of metabolic processes between the host and the parasite. Studies have shown that the accumulation of certain vitamins in the body of helminths depends on the concentration of vitamins absorbed in the digestive system of the host. Through the interaction between the host and the parasite, the helminths absorb the vitamins that are absorbed in the gut and intestines. Our research was based on the study of vitamins in parasitic tissues. Research in this area dates back to the forty-eighth century. They have done very little research in this area. We have used calorimetry, spectrophotometry, fluorometric methods and laboratory methods in our presentations.